Examining Ibn Sīnā’s and Suhrawardī’s Notion of the Soul: Reflections on Their Philosophical Contributions in the Modern Context - Muhammad Taufik; Awang, Jaffary; Abidin, Muhammad Zainal; Khairiyanto (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The intricate nature of contemporary human life has placed individuals in a paradoxical position, simultaneously serving as active agents shaping societal development and passive recipients of the outcomes of this evolution. The predominant emphasis on material and intellectual pursuits has, in some instances, resulted in the neglect of the soul as a bridge to the transcendent realm, often associated with the divine. Consequently, many modern individuals find themselves disconnected from their own existence and spiritual well-being. This research aims to address the real-world challenges faced by contemporary individuals by exploring the philosophical concepts of Ibn Sīnā and Suhrawadī, which hold significant relevance to the conditions of modern society. This study, utilizing a qualitative approach and a comparative synthesis analysis model, unveils a convergence in the conceptualization of the soul between Ibn Sīnā and Suhrawardī, particularly in their efforts to curb the influence of the animalistic soul (an-nafs al-hayāwanīyah). While their methodologies differ, reflecting their respective Aristotelian and illuminationist traditions, their shared objective remains unwavering. Ibn Sīnā emphasizes the rational soul (an-nafs al-naṭiqah) through acquired reason (al-'aql al-mustafad), striving to attain divine knowledge, a goal also pursued, albeit via a different path, by Suhrawardī through ascetic practices. The pursuit of maximal rationality and the adoption of ascetic practices offer modern individuals a potent means to combat the soul-crushing emptiness often associated with spiritual and existential crises.